The Influence of Online Promotion Strategy and Consumer Behavior on Purchase Interest at the Bandung City Employees Cooperative (KPKB Mart) in Bandung City - Sahrul Hidayat; Asep Zulkifli Achmad (Takaza Innovatix Labs Ltd., 2026)
Amid intense retail competition near Bandung City Hall, KPKB Mart faces challenges in digital promotion effectiveness despite high purchase intention among consumers. This study aims to analyze the influence of online promotional strategies and consumer behavior on purchase intention at KPKB Mart. A quantitative associative approach was employed with primary data from online questionnaires distributed to 95 consumers (convenience sampling from a 2000 population, September-November 2025). Data analysis included classical assumption tests, multiple linear regression, correlation, coefficient of determination (R²), and hypothesis testing (t-test, F-test) using SPSS. Results reveal a regression equation MB = 40.356 + 0.613SPO + 0.286PK, with strong correlations (r_SPO-MB = 0.820, r_PK-MB = 0.410), simultaneous effect (F = 78.738, p < 0.001, R² = 0.631), and partial effects (t_SPO = -12.181, t_PK = 4.634, both p < 0.001). Online promotions and consumer behavior significantly influence purchase intention, explaining 63.1% of variance. In conclusion, enhancing targeted digital promotions and understanding consumer patterns can optimize KPKB Mart's market position.